Distribution and community structure of Chaetodontidae (Perciformes) in iSimangaliso Wetland Park with the view to applying the Butterflyfish Indicator Hypothesis in this region of South Africa - Noble, Talitha Gaby (Department of Biological Sciences, 2015)
Includes bibliographical references.